Clinical pharmacist intervention reduces mortality in patients with acute myocardial infarction: a propensity score matched analysis. Issue 5 (14th March 2018) - Zhai, Xiao-Bo; Gu, Zhi-Chun; Liu, Xiao-Yan
Abstract : Background: Is it possible that the mortality rate from acute myocardial infarction (AMI) may decline after interventions by pharmacists? Objective: To evaluate the impact of clinical pharmacist on the mortality of AMI. Methods: Clinical pharmacists did not perform any interventions during phase 1 (pre-intervention), and consulted with physicians to address drug related problems (DRPs) during phase 2 (post-intervention). The main outcome was a decrease in mortality from AMI. The two phases were compared using propensity score matching (PSM). Results: 1388 interventions were suggested by clinical pharmacists during phase 2, of which 1239 (89.2%) were accepted. Logistic regression analysis demonstrated that interventions of clinical pharmacists were significantly associated with a reduced mortality in patients with both ST segment elevation myocardial infarction (STEMI) (OR 0.449; 95% CI 0.296 to 0.680) and non-ST segment elevation myocardial infarction (NSTEMI) (OR 0.268; 95% CI 0.125 to 0.572). Using PSM analysis, mortality reduced from 6.8% to 4.3% in STEMI patients (P=0.0034) and from 3.2% to 0.7% in NSTEMI patients (P=0.0202) after the interventions. Conclusions: DRPs that caused or contributed to possible mortality were detected by clinical pharmacists in patients with AMI. Correcting these DRPs after pharmacists' interventions could result in a significant decrease in mortality.